Mineralization of residue from the drying of black pepper when applied to the soil - Bosa, Igor Rozado; Lo Monaco, Paola Alfonsa Vieira; Haddade, Ismail Ramalho; Vieira, Gustavo Haddad Souza; Krause, Marcelo Rodrigo; Nandorf, Rodrigo Junior (Revista de Ciências Agroveterinárias, 2021)
The use of residues from the black pepper bean drying process as fertilizer for agricultural crops implies the need to know the dynamics of their decomposition and release of the nutrients to guide it’s management, especially regarding the best time of its application in the soil. This study aimed to evaluate the dynamics of organic carbon and nitrogen during the mineralization process of this residue. The experiment was conducted in a completely randomized design with ten treatments related to different post-disposal periods to the soil (0, 7, 13, 20, 27, 34, 48, 69, 98, 147 days). Samples were collected to quantify easily oxidized organic carbon (OCeo), organic nitrogen (ON) and the determinations of their respective mineralized fractions. The evaluation of OCeo mineralization, being more stable and less susceptible to climatic variations, was the most appropriate for estimating the mineralized fraction of the residue. The application of the residue in dystrophic Yellow Red Latosol soil during the month of August provides, after 140 days, OCeo and ON mineralized fractions around 99 and 60%, respectively, in the climatic conditions of Espirito Santo state, Brazil.